STUDI PENETAPAN KADAR LOSARTAN DENGAN METODE SPEKTROFOTOMETRI DAN HIGH PERFORMANCE LIQUID CHROMATOGRAPHY (HPLC) SERTA APLIKASINYA PADA TRANSPOR TRANSDERMAL in vitro - Binarjo, Annas; Nugroho, Achmad Kharis (Universitas Ahmad Dahlan, 2013)
The development of drug delivery system needs a usefull determination method ofdrug in many kind of samples. This research was purposed to develop a determinationmethod of losartan, an angiotension receptor antagonist II, from the sample of in vitrotransdermal transport. Three methods were studied, i.e. normal spectrophotometric, 1stderivative spectrophotometric, and HPLC. The spectrophotometric method wasconducted using Spectrophotometer Shimadzu tipe UV 1700 controlled by UV Probesoftware (Shimadzu), while HPLC method was performanced by Shimadzu HPLCcontrolled by LC Solution software (Shimadzu). Lichrospher RP 18 250-4 (5 Âµm) wasused as stationary phase and acetonitril-acetic buffer 0,01 M pH 4 (60:40) was used asmobile phase. Chromatogram was recorded using UV 223 nm and 254 nm as adetector. Some parameters of determination method performance were calculated, i.e.LOD, LOQ, recovery, systemic error, and random error. The results shown thatspectrofotometric methods did not have an enough performance parameters to use intransdermal transport of losartan, while HPLC method had LOD and LOQ 27,329 and91,098 ng/ml using UV 223 nm as detector and 36,178 and 120,590 ng/ml using UV 254nm as detector. Detector UV 223 nm was selected. This HPLC method had recovery106,405% and random error 3,71%, and could be used to determine the losartanconcentration in sample from transdermal transport in vitro.